Pemanfaatan Sarana Prasarana Olahraga Oleh Guru Pendidikan Jasmani Dalam Hubungannya Dengan Proses Belalar Mengajar - Hartianto, Naufal Dzaki; Juliantine, Tite; Mudjianto, Sufyar; Bahri, Samsul (Institut Teknologi Bandung, 2023)
The smooth learning of sports and health physical education is inseparable from the availability of adequate facilities and infrastructure. The existence of adequate facilities and infrastructure will reflect the quality of education, so that the goals of sports and health physical education will be achieved properly. But on the contrary, inadequate facilities and infrastructure will have an impact on the low quality of education, even the curriculum will not work. The method used is descriptive method. This research begins with observations made in schools. Data collection was carried out by giving questionnaires to predetermined respondents. The findings of this study mean the value of infrastructure utilization for the first respondent is 3.83, the second respondent is 3.60, and the third respondent is 3.80 with a standard deviation for the first respondent 1.58, the second respondent is 1.52 and the third respondent is 1.42. The result of the homogeneity test for the significance number is 0.642, meaning that H1 is acceptable and the data comes from a homogeneous population. The normality test results with a significance value of 0.00 means that H0 is rejected and the data has an abnormal distribution. The results of the hypothesis test using the Kruskal Wallis test with a significance number of 0.684 means that H1 is acceptable and there are significant differences in the ability of teachers to use physical education facilities and infrastructure. Based on the calculation data using the Tuckey test, respondents 1 and 2 have an average difference of 0.233 with a presentation of 23%, respondents 1 and 3 have an average difference of 0.33 with a presentation of 33%, and respondents 2 and 3 have an average of -0, 2 with a presentation - 20% has a P value. The value of respondents 1 and 2 is .821, respondents 1 and 3 are .996, and respondents 2 and 3 are .865 make all the data have a significant difference.